Physical properties of binary mixtures alcohol + ionic liquid at several temperatures and atmospheric pressure - Emilio J. González (2013)
In this study, densities and speeds of sound were measured over the wholecomposition range, at T = (298.15, 303.15 and 308.15) K and p = 0.1 MPa, for the binarysystems of ethanol, or 1-propanol, or 2-propanol and 1-butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide,or 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide.The density and speed of sound data were used to calculate the correspondingexcess molar volumes and excess molar isentropic compressions, which were fitted withthe RedlichKister equation. From the obtained results, a discussion was carried out interms of interactions and structure factors in these binary mixtures.